Early life programming of attention capacity in adolescents: The HELENA study. Issue 1 (11th April 2017) - Esteban‐Cornejo, Irene; Henriksson, Pontus; Cadenas‐Sanchez, Cristina; Vanhelst, Jérémy; Forsner, Maria; Gottrand, Frederic; Kersting, Mathilde; Moreno, Luis A.; Ruiz, Jonatan R.; Widhalm, Kurt; Ortega, Francisco B.; ,
Abstract: The study aims to examine the individual and combined association of early life factors (birth weight, birth length, and any and exclusive breastfeeding) with attention capacity in adolescents. The study included 421 European adolescents (243 girls), aged 12.5–17.5 years, who participated in the Healthy Lifestyle in Europe by Nutrition in Adolescence Study. Body weight and length at birth of adolescents were collected from parental records. The duration of any and exclusive breastfeeding were self‐reported. The d2 Test of Attention was administered to assess attention capacity. The main results showed that birth weight, birth length, breastfeeding, and exclusive breastfeeding were related to attention capacity in boys ( β ranging from 0.144 to 0.196; all p  < .05) after adjustment for age, centre, gestational age, maternal education, family affluence scale, and body mass index. Among boys, differences in attention capacity were found according to tertiles of birth weight and birth length ( p  < .05), as well as borderline significant differences across groups of any and exclusive breastfeeding ( p =  0.055 and p =  0.108, respectively) after adjusting for potential confounders. In addition, boys with 3 early life risk factors (low birth weight, low birth length, and <3 months of breastfeeding) had significantly lower scores in attention capacity compared with boys with 0 risk factors (percentile score − 15.88; p =  0.009). In conclusion, early life factors, both separately and combined, may influence attention capacity in male European adolescents. Importantly, the combination of the 3 early life risk factors, low birth weight, low birth length, and <3 months of breastfeeding, even in normal ranges, may provide the highest reduction in attention capacity.